Central Asian security : the new international context - Allison, Roy; Jonson, Lena, 1948- (Royal Institute of International Affairs ; Brookings Institution Press, 2001)
"The authors in this study assess internal security policy problems and examine the security content of evolving relations between the Central Asian states and regional and international powers - specifically the stakes, interests, and policies of Russia, China, Iran, Turkey, and the United States. While new possibilities for regional security cooperation in Central Asia can be explored, there remains a danger of destabilizing rivalry, which would fracture the region and hamper economic development. These dilemmas are examined by a team of specialists from Western Europe, the United States, Russia, and China."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
"In association with the Swedish Institute of International Affairs."
Keywords: National security -- Asia, Central.; Asia, Central -- Foreign relations -- 1991-; Asia, Central -- Strategic aspects.; Sécurité régionale -- Asie centrale.; Asie centrale -- Relations extérieures -- 1991-; Asie centrale -- Aspect stratégique.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; POLITICAL SCIENCE -- International Relations -- Diplomacy.; Diplomatic relations; National security; Strategic aspects of individual places; Central Asia; Buitenlandse politiek.; Veiligheidspolitiek.; Internationale veiligheid.; Nationale veiligheid.; Internationale samenwerking.; Militaire samenwerking.; Midden-Azië; Since 1991; Samfundsvidenskab -- Politologi.